2009
DOI: 10.1254/jphs.08308fp
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Attenuates Neointimal Formation by Inhibiting Reactive Oxygen Species–Mediated Responses in Vascular Smooth Muscle Cells in Rats

Abstract: Abstract. We determined the action mechanism of cordycepin, a major bioactive component of Cordyceps militaris, on responses of rat aortic smooth muscle cells (RASMCs) and on vascular disorders, especially neointimal formation. Cordycepin inhibited platelet-derived growth factor-BB (PDGF-BB)-induced RASMCs migration and proliferation in a dose-dependent manner. However, pre-treatment with N ω -nitro-L-arginine methyl ester, a nitric oxide synthase (NOS) inhibitor, and 1,3-dipropyl-8-sulphophenylxanthine (DPSPX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…Natural products, which have been traditionally used in the treatment of inflammatory disease, are considered novel and effective biological agents (10)(11)(12)(13). To develop novel therapeutic agents, it is important to investigate the mechanism regulating inflammatory signal reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products, which have been traditionally used in the treatment of inflammatory disease, are considered novel and effective biological agents (10)(11)(12)(13). To develop novel therapeutic agents, it is important to investigate the mechanism regulating inflammatory signal reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cordyceps spp., whose main chemical constituent is cordycepin, have also been demonstrated to confer anti-inflammatory effects. Won et al reported that cordycepin attenuated neointimal formation by inhibiting reactive oxygen species (ROS)-mediated responses in vascular smooth muscle cells in rats (11). Moreover, some studies have reported that the natural component specifically inhibited the transcriptional activity in the cytokine-stimulated pro-inflammatory response (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Some drugs are also known to contract smooth muscle 2,3) . Many previous studies, including our own, have reported on signal transduction mechanisms and smooth muscle contractions [4][5][6][7][8][9][10][11][12][13][14] . In spite of the importance of the smooth muscle in the fields of cardiovascular physiotherapy, obstetrics, and clinical methods, there is still a need for more research [15][16][17] .…”
Section: Introductionmentioning
confidence: 89%
“…This contraction pathway begins with the activation of GTP-binding proteins by an external stimulus. The external stimulus activates the acceptor resulting in the activation of the α-subunit of trimeric G-protein such as Gα q , Gα 12,13 , and Gα i-2 . The activated Gα-subunit activates Rho guanine nucleotide exchange factor (Rho GEF) 45) .…”
Section: ) Rho-associated Coiled Coil-forming Protein Kinase (Rock) mentioning
confidence: 99%
“…Although some herbal medicines have been used for the prevention or treatment of cardiovascular diseases like atherosclerosis (Mashour et al, 1998), there are no reports of CBMF being used to treat vascular disorders. Since there are many reports about other herbal extracts inhibiting VSMC migration and proliferation that are key events in neointima formation (Choi et al, 2009;Won et al, 2009), we here explored whether CBMF floral water (CBMFF) could affect PDGF-BB-induced proliferation and migration of rat aortic smooth muscle cells (RASMCs).…”
Section: Introductionmentioning
confidence: 99%